Discourse functions of lexical bundles in Pakistani chemistry and physics textbooks - Hussain, Gulfam; Zahra, Tehseen; Abbas, Akhtar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lexical bundles (LBs) are indispensable building blocks and essential constituents of academic discourse. The appropriate utilization of the lexical bundle’s approach can effectively enhance students’ understanding of academic discourse. LBs in various academic genres have extensively been studied concerning written and spoken language. However, less research has been conducted to explore the occurrence, nature, and frequency of LBs in Pakistani academic discourse, especially in textbooks. Therefore, the present study aims to explore four-word common LBs and their functional taxonomies employed in Pakistani Higher Secondary School Certificate (HSSC) level textbooks of Chemistry and Physics. A specialized corpus of these textbooks was built which was run on Antconc software for the identification and extraction of the LBs in the corpus. The classification of the identified LBs was then carried out utilizing Biber functional taxonomies of LBs. The study found 102 LBs occurring in the selected textbooks. In functional categories, there was a dominant use of discourse organizers and referential expressions. The findings related to frequent strings of words which can have significant educational implications for teachers, language material developers, and syllabus designers. The list of LBs with discourse functions provided by this study can significantly be used to enhance students’ academic writing and their ability to comprehend different types of scientific texts.